Reliability enhenced resource reservation strategy in computing grid - DING Chang-song1; HU Zhi-gang1; XIAO Peng3 (Tongxin xuebao, 2011)
A stochastic model was used to describe reservation service of grid resources and an approach calculating re-liability-guarantee expressed as probability guarantee success rate was proposed for reservation requests.By the approach,a reliability-enhenced reservation strategy was proposed.Experimental results show that the proposed strategy can sig-nificantly improve resource utilization.Also,it is able to reduce the jobs’ violation rate comparing to conventional reser-vation policy,with respect to adaptability to dynamic grid environment.